2022 revised European recommendations for the coding of the basis of diagnosis of cancer cases in population-based cancer registries - Visser, Otto; Kościańska, Beata; Caetano dos Santos, Florentino Luciano; Cuccaro, Francesco; Forjaz, Gonçalo; Michalek, Irmina Maria; Mousavi, Mohsen; Sulkowska, Urszula; Martos, Carmen; Giusti, Francesco (Frontiers in Oncology, 2023)
The basis of diagnosis recommendations for population-based cancer registries aim to provide a standardised coding tool that reflects the certainty of cancer diagnosis, especially when pathological confirmation is lacking. The proportion of clinical diagnoses serves as an indicator of data quality. Given the evolving nature of diagnostic techniques, regular revision of the basis of diagnosis rules is crucial.To address this, a working group comprising representatives from the steering committee and member registries of the European Network of Cancer Registries was established. The original 1999 recommendations were comprehensively reviewed, resulting in the publication of an updated version. These new recommendations came into effect for incident cancer cases starting from January 1, 2023.The updated recommendations comprise an adapted code list for the basis of diagnosis, optional codes for histology cases, revisions related to flow cytometry, liquid biopsy, and cytogenetic/molecular testing, consolidation of histology codes 6 and 7, introduction of a new code 8 for cytogenetic/molecular confirmation, and establishment of new criteria for registering specific morphology codes in cancers lacking pathological confirmation.The updated recommendations make a valuable contribution by improving the accuracy of coding the basis of diagnosis, which is a quality indicator for cancer registries. Registries with a distribution that differs from the expected distribution are considered of lower quality. However, this quality indicator can only be used if the basis of diagnosis is coded correctly. Therefore, these recommendations contribute to a more reliable quality indicator and, consequently, increase the reliability of cancer registry data. Furthermore, the recommendations include rules for coding the morphology of cases without pathological confirmation. Especially for central nervous system tumours, only diagnosis based on imaging is often available. As there are large differences in the clinical behaviour of these tumours, a more detailed classification of these tumours is required. This will greatly improve the comparability between registries of tumours without pathological confirmation, especially in the central nervous system.